New Evidences on Anomalous Phenomenon of Buildings in Regulating Urban Climate From Observations in Beijing, China. Issue 5 (28th May 2019) - Kuang, Wenhui
Abstract: Urban buildings and parks play an important role in regulating urban climate and ecosystem services. Diurnal air temperature range (DTRa ) of rocklike buildings is commonsensically regarded as higher due to no latent heat from evapotranspiration and its smaller thermal inertia compared to wet soil. Therefore, the building DTRa is supposed to be higher than that of parks due to its building fabric. However, we found an opposite phenomenon (smaller building DTRa than that of parks), and the underlying mechanisms explaining this phenomenon are unclear. Here we conducted, in Beijing (China), a long‐term observational campaign of standard meteorological variables and radiation/energy fluxes to provide a new valuable evidence (a part of external energy) to explain this phenomenon. The observations indicated external heat energies from horizontal advection and anthropogenic heat sources. We found a significantly lower building DTRa than that of parks (ΔDTRa =2.53±1.93 °C), with a maximum difference of 3.54±1.96 °C in autumn; which was mainly attributed to higher daily minimum air temperature. We also found the large differences in air temperature contribution between the buildings and the parks happened mainly at night. The external heat sources of the building contributed 16.71% to the nighttime air temperature, which was higher than that of the parks (8.39%). The more indoor and outdoor anthropogenic heat sources in the building footprints were the major cause of the slower decrease in T min . The comparison between buildings and parks can be extensively applied to analyzing the effects of urbanization on climate. Plain Language Summary: An effective mosaic of buildings and parks, as the two core elements of cities, plays an important role in regulating urban climate and providing ecosystem services. A comfortable urban environment is becoming the pivotal theme for the United Nations Sustainable Development Goals 2030 related to resilient and sustainable cities and to mitigate climate change. While the urbanization effect on the diurnal air temperature range (DTRa ) is still being debated within the climate community, we, surprisingly, found a significantly lower DTRa of buildings than of parks, which contradicts our common knowledge. The observations showed that nocturnal radiation cooling did not result in a decrease of air temperature, largely due to external heat input (60.17±22.98 W/m 2 ). Heat fluxes of both the building roofs from their large indoor heat sources and the mixed peripheral advection with anthropogenic heat discharges contributed to a higher minimum air temperature. In daytime, despite additional input from human‐induced energy, neighboring vegetation transpiration and building/tree shadows offset those heat fluxes and slowed down the air temperature increase. The findings provide new knowledge on urban heat island mitigation and climate change adaptation. Key Points: The diurnal air temperature range of buildings is significantly lower than that of parks (ΔDTRa = 2.53±1.93 °C) The lower diurnal air temperature range of buildings compared to parks is attributed to a higher daily minimum air temperature The contribution of external heat sources by buildings (16.71%) to the nighttime air temperature was twice that of the park (8.39%)